DEVELOPMENT ANALYSIS OF QUACULTURE VILLAGE IN GARUT REGENCY - Anindya Pratami Putri; Iwang Gumilar (AQUASAINS, 2023)
This study aims to identify issues and formulate strategies related to the development of aquaculture village areas in Garut Regency. This research was conducted for 2 months, namely August-October. Methods of data collection by observation and interviews. Data analysis using SWOT analysis. Garut Regency has the potential for freshwater aquaculture covering an area of 26,000 hectares which includes aquaculture of calm water ponds, swift water ponds and rice fields. The aquaculture village is a program from the Ministry of Maritime Affairs and Fisheries (KKP) which aims to improve the local rural economy for the period 2021-2024. The application of the concept of developing aquaculture villages is a strategic step in the implementation of marine and fisheries development. Aquaculture village is an area based on superior commodities and local commodities, which can encourage the development of competitive and sustainable fish farming, as well as protect fish resources and ensure sustainable and planned production. The results of the SWOT analysis show that an important strategy in developing aquaculture village areas in Garut Regency is to take advantage of market opportunities, government development supervision and community participation.